ANALISIS PROSES RESTITUSI PAJAK PERTAMBAHAN NILAI PADA PT. XYZ - Juaniva Sidharta; Lenny Panggabean; , Gilbert Louis Antonio (Buletin Ekonomi, 2023)
VAT Refund is the right of the taxpayer to re-request the overpayment of taxes to the state. There are various ways that can be done in applying for VAT Restitution. That is by going through General Mechanisms and Special Mechanisms. These methods have their own advantages and disadvantages that can be used by taxpayers to get a refund of excess tax. PT. XYZ is a PKP that has an overpayment of taxes and submits an application for restitution by following the existing process. The purpose of this writing is to find out the VAT restitution process submitted is in accordance with the applicable Tax Law, find out the obstacles faced in applying for the VAT restitution process, find out how the process of completing the VAT Refund submitted by PT. XYZ. This type of research is descriptive research with a qualitative approach through data collection methods in the form of interviews, documentation. Keywords : Restitution, Value Added Tax.